2021
DOI: 10.3390/ijerph18157960
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Damage Biomarkers in Congestion Weeks in English Premier League Soccer Players: A Prospective Study for Two Consecutive Seasons

Abstract: The current study was conducted to compare muscle damage biomarkers in single- vs. multi-match weeks in elite soccer players for two consecutive seasons. A secondary objective was to analyze the influence of playing position and exposure time on muscle damage in single- vs. multi-match weeks. This is a prospective cohort study performed in a professional elite soccer club in the English Premier League during the 2018–2019 and 2019–2020 seasons up until the lockdown due to the COVID-19 pandemic. Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Precisely, CK levels have been used to monitor muscle damage and post-match neuromuscular fatigue in elite football players [ 51 ] and other sports [ 49 , 50 ]. Most studies have reported data from single-match experiments [ 52 ] or short-term studies [ 53 ] and much less information is available on long-term studies during the entire season in elite professional football [ 54 ]. In the present study, in T2, T3, and T4 of both seasons, CK values were slightly above 270 U·L −1 , set as the highest reference value for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Precisely, CK levels have been used to monitor muscle damage and post-match neuromuscular fatigue in elite football players [ 51 ] and other sports [ 49 , 50 ]. Most studies have reported data from single-match experiments [ 52 ] or short-term studies [ 53 ] and much less information is available on long-term studies during the entire season in elite professional football [ 54 ]. In the present study, in T2, T3, and T4 of both seasons, CK values were slightly above 270 U·L −1 , set as the highest reference value for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the analysis of capillary blood permits a simple, inexpensive, and less invasive sampling process, significant heterogeneities between capillary and venous biomarker levels have been documented (Reichel et al, 2023). Additionally, some analytes, such cortisol and testosterone, are subject to important circadian variations, highlighting the importance of considering the timing of sampling (Gabriel and Zierath, 2019). Changes in inflammatory and immune biomarkers might reflect infection and other nonexercise-related inflammatory processes, so evaluating the player's health status is important when monitoring these markers (Lee et al, 2017).…”
Section: Role Of Sportomics In Post-match Recoverymentioning
confidence: 99%
“…Regarding football, a vast number of studies conducted in male and female semi-professional and professional football players have reported values of CK as a means to assess EIMD in training and competition ( Andersson et al, 2008 ; Gravina et al, 2011 ; Rampinini et al, 2011 ; Thorpe and Sunderland, 2012 ; Gatterer et al, 2013 ; Gunnarsson et al, 2013 ; Nedelec et al, 2013 ; Silva et al, 2013 ; Souglis et al, 2015a ; Pimenta et al, 2015 ; Russell et al, 2015 ; Mohr et al, 2016 ; Bouzid et al, 2018 ; Henrique et al, 2018 ; Marques-Jimenez et al, 2018 ; Souglis et al, 2018 ; Sparkes et al, 2018 ; Botelho et al, 2020 ; Pooley et al, 2020 ; Chou et al, 2021 ; Csala et al, 2021 ; Daab et al, 2021 ; Garcia-Romero-Perez et al, 2021 ; Hacker et al, 2021 ; Khaitin et al, 2021 ; Kostrzewa-Nowak et al, 2021 ; Trecroci et al, 2021 ; Selmi et al, 2022 ). Of note, as susceptibility to EIMD is higher among players unaccustomed to eccentric exercise, returning to high-intensity training and competition from off-season and periods of recovery from injury are considered critical time points for monitoring ( Nédélec et al, 2012 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher risk of injury caused by 3–4-day intervals between mathes, probably because the fatigue level of players is higher than a single match in a week. The English Premier League players played 4 days apart from one another, and creatine kinase levels and fatigue levels before the second match were significantly higher than those found when they were playing a match per week [ 43 ]. Athletes’ subjective health, overall quality of recovery, and adductor strength required at least 96 h to recover in the event of more than one match per week [ 44 ].…”
Section: Discussionmentioning
confidence: 99%